Cellobiose dehydrogenase functionalized urinary catheter as novel antibiofilm system. Issue 7 (6th August 2015) - Thallinger, Barbara; Brandauer, Martin; Burger, Peter; Sygmund, Christoph; Ludwig, Roland; Ivanova, Kristina; Kun, Jutta; Scaini, Denis; Burnet, Michael; Tzanov, Tzanko; Nyanhongo, Gibson S.; Guebitz, Georg M.
Abstract: Urinary catheters expose patients to a high risk of acquiring nosocomial infections. To prevent this risk of infection, cellobiose dehydrogenase (CDH), an antimicrobial enzyme able to use various oligosaccharides as electron donors to produce hydrogen peroxide using oxygen as an electron acceptor, was covalently grafted onto plasma‐activated urinary polydimethylsiloxane (PDMS) catheter surfaces. Successful immobilization of CDH on PDMS was confirmed by Fourier transformed‐infrared spectrometry and production of H2 O2 . The CDH functionalized PDMS surfaces reduced the amount of viable Staphylococcus aureus by 60%, total biomass deposited on the surface by 30% and 70% of biofilm formation. The immobilized CDH was relatively stable in artificial urine over 16 days, retaining 20% of its initial activity. The CDH coated PDMS surface did not affect the growth and physiology of HEK 239 and RAW 264, 7 mammalian cells. Therefore this new CDH functionalized catheter system shows great potential for solving the current problems associated with urinary catheters. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1448–1456, 2016.